Supplementation with Lactobacillus plantarum WCFS1 Prevents Decline of Mucus Barrier in Colon of Accelerated Aging Ercc1−/Δ7 Mice - van Beek, Adriaan A.; Sovran, Bruno; Hugenholtz, Floor; Meijer, Ben; Hoogerland, Joanne A.; Mihailova, Violeta; van der Ploeg, Corine; Belzer, Clara; Boekschoten, Mark V.; Hoeijmakers, Jan H. J.; Vermeij, Wilbert P.; de Vos, Paul; et al. (Frontiers in Immunology, 2016)
Although it is clear that probiotics improve intestinal barrier function, little is known about the effects of probiotics on the aging intestine. We investigated effects of 10-wk bacterial supplementation of Lactobacillus plantarum WCFS1, Lactobacillus casei BL23, or Bifidobacterium breve DSM20213 on gut barrier and immunity in 16-week-old accelerated aging Ercc1-/Δ7 mice, which have a median lifespan of ~20wk, and their wild-type littermates. The colonic barrier in Ercc1-/Δ7 mice was characterized by a thin (<10µm) mucus layer. L. plantarum prevented this decline in mucus integrity in Ercc1-/Δ7 mice, whereas B. breve exacerbated it. Bacterial supplementations affected the expression of immune-related genes, including Toll-like receptor 4. Regulatory T cell frequencies were increased in the mesenteric lymph nodes of L. plantarum- and L. casei-treated Ercc1-/Δ7 mice. L. plantarum- and L. casei-treated Ercc1-/Δ7 mice showed increased specific antibody production in a T cell-dependent immune response in vivo. By contrast, the effects of bacterial supplementation on wild-type control mice were negligible. Thus, supplementation with L. plantarum – but not with L. casei and B. breve – prevented the decline in the mucus barrier in Ercc1-/Δ7 mice. Our data indicate that age is an important factor influencing beneficial or detrimental effects of candidate probiotics. These findings also highlight the need for caution in translating beneficial effects of probiotics observed in young animals or humans to the elderly.